Perovskite solar cell based on multifunctional additive and preparation method thereof
By adding multifunctional additives to the perovskite precursor solution of perovskite solar cells, the film quality problems caused by humidity and oxygen in solution preparation are solved, and efficient, stable and repeatable perovskite solar cell preparation is achieved.
Patent Information
- Application Number
- CN202411768429.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-15
AI Technical Summary
When preparing perovskite solar cell thin films by solution method, humidity and oxygen lead to uncontrollable crystallization process, poor crystal quality, and untightened coverage, resulting in limited battery efficiency and stability.
Multifunctional additives are used, and the general structure formula is X·Y, where X is a hydrazine compound and Y is a reducing acid compound. It is added to the perovskite precursor solution to inhibit oxidation and iodine element formation, improve the film formation quality of the thin film, and improve the battery performance through defect passivation.
It significantly improves the efficiency, stability and process reproducibility of perovskite solar cells, extends the stability of the use of perovskite precursor solutions, and reduces the sensitivity of preparation environmental conditions.
Smart Images

Figure CN119836205A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a perovskite solar cell based on a multifunctional additive and a preparation method thereof. Background Art
[0002] Organic-inorganic hybrid perovskite materials have attracted the attention of many researchers due to their excellent photoelectric properties, low cost, and wide sources. The photoelectric conversion efficiency of perovskite solar cells has soared from 3.8% in 2009 to 26.7% in 2024, catching up with the level of crystalline silicon solar cells currently on the market. It is considered to be the third-generation solar cell with the most commercial potential.
[0003] However, the solution method for preparing high-quality perovskite films usually requires strict environmental control, because humidity can cause the perovskite film to have problems such as uncontrollable crystallization process, poor crystal quality, and loose coverage. Oxygen will accelerate the oxidation of iodine ions dissociated from organic ammonium salts in the perovskite precursor solution into elemental iodine, causing the perovskite precursor solution to deteriorate, the defect state density of the prepared perovskite film to increase, and the non-radiative recombination of carriers to intensify. The dual effects of water and oxygen lead to a significant reduction in the quality of the perovskite film, limiting the efficiency and stability of perovskite solar cells. In addition, nickel oxide hole transport layers are usually used in traditional inverted perovskite solar cells. The presence of high-valent nickel ions on the surface of nickel oxide will also oxidize iodine ions in the perovskite precursor solution to form defect-induced recombination centers, affecting the consistency of battery preparation and hindering the mass production and commercial application of perovskite solar cells. Summary of the invention
[0004] The purpose of the present invention is to avoid the shortcomings of the prior art and provide a perovskite solar cell based on a multifunctional additive and a preparation method thereof, wherein the multifunctional additive is used to reduce the adverse effect of moisture on perovskite crystallization, inhibit the oxidation of the perovskite precursor solution, eliminate the formation of iodine, improve the film quality of the perovskite light-absorbing layer, and at the same time superimpose the defect passivation effect of the multifunctional additive, thereby greatly improving the efficiency, stability and process reproducibility of the perovskite solar cell.
[0005] According to a first aspect of an embodiment of the present application, a perovskite solar cell based on a multifunctional additive is provided, wherein the perovskite solar cell comprises, from bottom to top, a transparent conductive substrate layer, a hole transport layer, a perovskite light absorption layer, an electron transport layer, an interface buffer layer and an electrode layer, wherein the perovskite light absorption layer contains a multifunctional additive;
[0006] The general structural formula of the multifunctional additive is X·Y, wherein X is a hydrazine compound, including one of phenylhydrazine, benzylhydrazine, phenethylhydrazine, phenylpropylhydrazine, benzoylhydrazine, and phenylacetylhydrazine; Y is a reducing acid compound, including formic acid, hypophosphorous acid, benzenesulfinic acid, methanesulfinic acid, 2,4-hexadienoic acid, 5-phenyl-2,4-pentadienoic acid, 2,4,6,8-decatetraenoic acid, 3,4,5-trihydroxybenzoic acid, 3,5-dihydroxyphenylacetic acid, 4-hydroxyphenylacetic acid, p-hydroxybenzoic acid, 3,5-dihydroxybenzoic acid, preferably one of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate.
[0007] Furthermore, the transparent conductive substrate layer is made of FTO (fluorine-doped tin oxide) glass, ITO (tin-doped indium oxide) glass, ITO (tin-doped indium oxide) / PET (ethylene terephthalate), ITO (tin-doped indium oxide) / PEN (polyethylene phthalate) or ITO (tin-doped indium oxide) / PI (polyimide), preferably FTO glass.
[0008] Furthermore, the hole transport layer uses nickel oxide or nickel oxide doped with Mg, Li, Cs, Cu, Zn, Sr, and Co, preferably 3% Cu-doped nickel oxide, which has higher transmittance, higher conductivity, and more matched energy bands than undoped nickel oxide, and has a thickness of 1 to 100 nm, preferably 40 nm.
[0009] Furthermore, the perovskite light absorbing layer has a general structural formula of ABX3 and a thickness of 100 to 2000 nm, preferably 500 nm, wherein A is Cs + 、MA + (CH3NH3 + ) or FA + [HC(NH2)NH2 + ], B is Pb 2+ Sn 2+ Or Ge 2+ , X is I - Br - or Cl - .
[0010] Furthermore, the electron transport layer is fullerene and its derivatives, including but not limited to C60, C70, PC60M, etc., preferably C60, with a thickness of 1 to 100 nm, preferably 50 nm.
[0011] Furthermore, the interface buffer layer is made of bathocuproin, tin oxide, zinc oxide, yttrium oxide, cerium oxide, titanium oxide or niobium oxide, preferably tin oxide, and has a thickness of 1 to 100 nm, preferably 10 nm.
[0012] Furthermore, the electrode layer is Cu, Ag, Au, Mo, ITO (tin-doped indium oxide), IZO (zinc-doped indium oxide) or AZO (aluminum-doped zinc oxide), preferably IZO, and has a thickness of 10 to 10000 nm, preferably 500 nm.
[0013] According to a second aspect of an embodiment of the present application, a method for preparing a perovskite solar cell based on a multifunctional additive as described in the first aspect is provided, comprising:
[0014] (1) Synthesize multifunctional additives;
[0015] (2) depositing a hole transport layer on a clean transparent conductive substrate layer;
[0016] (3) dissolving the perovskite powder in an organic solvent, stirring and clarifying to form a perovskite precursor solution, adding a multifunctional additive, and dissolving it completely to obtain a perovskite precursor solution containing the multifunctional additive, coating or printing the perovskite precursor solution containing the multifunctional additive on the hole transport layer and heat treating it to obtain a perovskite light absorbing layer;
[0017] (4) An electron transport layer, an interface buffer layer, and an electrode layer are sequentially deposited on the perovskite light absorbing layer to obtain a perovskite solar cell based on a multifunctional additive.
[0018] Furthermore, in step (2), the hole transport layer is deposited by a method selected from evaporation, sputtering, chemical vapor deposition, coating, and printing, preferably sputtering deposition.
[0019] Furthermore, in step (3), the organic solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol, and acetonitrile, preferably 2-methoxyethanol and N-methylpyrrolidone (volume ratio of 9:1), the concentration of the perovskite precursor solution is 0.1-3 mol / L, preferably 1.2 mol / L, the concentration of the multifunctional additive in the perovskite precursor solution containing the multifunctional additive is 0.001-50 mg / mL, preferably 3 mg / mL, the heat treatment temperature is 30-300°C, the time is 0-120 minutes, preferably 120°C for 20 minutes.
[0020] Furthermore, in step (4), the electron transport layer is deposited by evaporation, the interface buffer layer is deposited by evaporation, sputtering, reactive plasma deposition, chemical vapor deposition, coating, and printing, preferably reactive plasma deposition, and the electrode layer is deposited by evaporation, sputtering, chemical vapor deposition, coating, and printing, preferably sputtering deposition.
[0021] The technical solution provided by this application may have the following beneficial effects:
[0022] 1. The present invention uses a multifunctional additive to improve the long-term use stability of the perovskite precursor solution, and utilizes the antioxidant properties of hydrazine compounds to not only delay the oxidation of the perovskite precursor solution by oxygen in the environment, thereby improving the utilization rate of the solution, but also inhibits the oxidation process of high-valent nickel on the surface of the nickel oxide hole transport layer, passivates interface defects, eliminates interface energy band barriers, releases residual stress of the perovskite film, and constructs a stable and unobstructed interface charge transfer channel to improve the efficiency of the device. In addition, the nitrogen atoms in the additive can interact with the body defects of the perovskite film, thereby inhibiting the non-radiative recombination of carriers and further improving the photoelectric conversion efficiency.
[0023] 2. The multifunctional additive of the present invention is added to the perovskite precursor solution, and the organic oxygen-containing acid in the additive chelates with the lead ions in the perovskite precursor solution to form a strong Pb=O coordination bond and a weak Pb-I bond, which hinders the coordination effect of water molecules in the crystallization process, promotes the preferential orientation growth of perovskite crystals, significantly improves the quality of perovskite films prepared in a humidity environment, greatly reduces the sensitivity of the environmental conditions for the preparation of perovskite batteries, and improves the photoelectric conversion efficiency and stability.
[0024] 3. The perovskite solar cell regulated by the multifunctional additives of the present invention has the advantages of high photoelectric conversion efficiency, good long-term working stability, and high preparation repeatability.
[0025] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0027] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell based on phenylacetylhydrazine·5-phenyl-2,4-pentadienoate of the present invention;
[0028] Figure 2 The diagram is a color change diagram of the perovskite precursor solution with or without phenylacetylhydrazine·5-phenyl-2,4-pentadienoate of the present invention when placed in the air for different time periods;
[0029] Figure 3 The graph is a graph showing the change in absorbance intensity of the perovskite precursor solution with or without phenylacetylhydrazine·5-phenyl-2,4-pentadienoate of the present invention when placed in the air for different time periods;
[0030] Figure 4 The figure is a relationship between the efficiency of the perovskite solar cell with or without phenylacetylhydrazine·5-phenyl-2,4-pentadienoate and the time the perovskite precursor solution is placed in the air;
[0031] Figure 5 A graph showing the relationship between the efficiency of the perovskite solar cell with or without phenylacetylhydrazine·5-phenyl-2,4-pentadienoate and the humidity of the preparation environment;
[0032] Figure 6 The SEM image of the perovskite light absorbing layer with or without phenylacetylhydrazine·5-phenyl-2,4-pentadienoate deposited on the copper-doped nickel oxide hole transport layer of the present invention;
[0033] Figure 7 The XPS graph of the hole transport layer of copper-doped nickel oxide with or without modification of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate of the present invention;
[0034] Figure 8 The XRD diagrams of the perovskite light absorbing layer with or without phenylacetylhydrazine·5-phenyl-2,4-pentadienoate deposited on the copper-doped nickel oxide hole transport layer of the present invention after being placed for different time periods. DETAILED DESCRIPTION
[0035] Here, exemplary embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application.
[0036] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0037] It should be understood that although the terms first, second, third, etc. may be used in the present application to describe various information, these information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of the present application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Depending on the context, the word "if" as used herein may be interpreted as "at the time of" or "when" or "in response to determining".
[0038] The existing battery basic structure involved in the present invention includes a transparent conductive substrate layer, a hole transport layer, a perovskite light absorption layer, an electron transport layer, an interface buffer layer, and an electrode layer in sequence. When the traditional perovskite precursor solution is deposited on the hole transport layer in the air, problems such as small grains, multiple grain boundaries, large surface roughness, and large interface residual stress will occur, which seriously affect the transmission and extraction of carriers. There are a large number of defects at the surface interface of the perovskite film, which will also induce non-radiative recombination of carriers, reducing the photoelectric conversion efficiency of the device.
[0039] In order to solve the above problems, the present invention provides the following specific implementation methods.
[0040] Example:
[0041] like Figure 1 As shown, a method for preparing a perovskite solar cell (nickel oxide type) based on a multifunctional additive comprises the following steps:
[0042] (1) 150.18 mg (1 mmol) of phenylacetyl hydrazine was weighed and dissolved in 15 mL of anhydrous ethanol, 174.196 mg (1 mmol) of 5-phenyl-2,4-pentadienoic acid was weighed and dissolved in 2 mL of anhydrous ethanol, and the 5-phenyl-2,4-pentadienoic acid ethanol solution was slowly added dropwise to the continuously stirred phenylacetyl hydrazine ethanol solution. The reaction temperature was kept at zero degrees during the reaction process, and nitrogen was introduced for protection. After the addition was completed, stirring was continued for 20 minutes, and phenylacetyl hydrazine·5-phenyl-2,4-pentadienoic acid crude product was obtained by rotary evaporation. Finally, the crude product was washed four times with ethyl acetate and ether in turn to obtain pure phenylacetyl hydrazine·5-phenyl-2,4-pentadienoic acid salt (263 mg, yield 81%), which was vacuum dried for 16 hours and then used for later use;
[0043] (2) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water, and alcohol in sequence, and drying the FTO glass after cleaning to obtain a clean FTO glass substrate; sputtering a 3% Cu-doped nickel oxide target on the clean FTO glass substrate layer to obtain a 40 nm nickel oxide hole transport layer;
[0044] (3) First, weigh CsI, MAI, FAI, and PbI2 (molar ratio of 0.05:0.15:0.8:1.08) powders and dissolve them in a mixed solvent of 2-methoxyethanol and N-methylpyrrolidone (volume ratio of 9:1). Stir to clarify to obtain a 1.2 mol / L perovskite precursor solution. Then weigh 3 mg of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate and add it to 1 mL of the perovskite precursor solution. Stir to completely dissolve to obtain a perovskite precursor solution containing phenylacetylhydrazine·5-phenyl-2,4-pentadienoate additives. Slit-coat the perovskite precursor solution containing phenylacetylhydrazine·5-phenyl-2,4-pentadienoate additives on a substrate covered with a nickel oxide hole transport layer. The coated perovskite wet film is heat treated at 120°C for 20 min to obtain a 500 nm thick perovskite light absorbing layer.
[0045] (4) A 50 nm thick C60 electron transport layer is sequentially evaporated on the perovskite light absorbing layer, a 10 nm thick tin oxide interface buffer layer is reactively plasma deposited, and a 500 nm thick IZO electrode layer is sputtered to obtain a perovskite solar cell based on the multifunctional additive of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate.
[0046] Comparative Example 1:
[0047] A perovskite solar cell (nickel oxide type) without multifunctional additives and a preparation method thereof, comprising the following steps:
[0048] (1) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water and alcohol in sequence, and drying after cleaning to obtain a clean FTO glass substrate; sputtering a 3% Cu-doped nickel oxide target on the clean FTO glass substrate layer to obtain a 40 nm nickel oxide hole transport layer;
[0049] (2) Weighing CsI, MAI, FAI, and PbI2 powders (molar ratio of 0.05:0.15:0.8:1.08) and dissolving them in a mixed solvent of 2-methoxyethanol and N-methylpyrrolidone (volume ratio of 9:1), stirring and clarifying to obtain a 1.2 mol / L perovskite precursor solution; slit coating the perovskite precursor solution on a substrate covered with a nickel oxide hole transport layer, and heat treating the coated perovskite wet film at 120°C for 20 min to obtain a 500 nm thick perovskite light absorbing layer;
[0050] (3) A 50 nm thick C60 electron transport layer is sequentially evaporated on the perovskite light absorbing layer, a 10 nm thick tin oxide interface buffer layer is reactively plasma deposited, and a 500 nm thick IZO electrode layer is sputtered to obtain a perovskite solar cell without multifunctional additives.
[0051] Comparative Example 2:
[0052] A multifunctional additive interface-modified perovskite solar cell (nickel oxide type) and a preparation method thereof, comprising the following steps:
[0053] (1) 150.18 mg (1 mmol) of phenylacetyl hydrazine was weighed and dissolved in 15 mL of anhydrous ethanol, 174.196 mg (1 mmol) of 5-phenyl-2,4-pentadienoic acid was weighed and dissolved in 2 mL of anhydrous ethanol, and the 5-phenyl-2,4-pentadienoic acid ethanol solution was slowly added dropwise to the continuously stirred phenylacetyl hydrazine ethanol solution. The reaction temperature was kept at zero degrees during the reaction process, and nitrogen was introduced for protection. After the addition was completed, stirring was continued for 20 minutes, and phenylacetyl hydrazine·5-phenyl-2,4-pentadienoic acid crude product was obtained by rotary evaporation. Finally, the crude product was washed four times with ethyl acetate and ether in turn to obtain pure phenylacetyl hydrazine·5-phenyl-2,4-pentadienoic acid salt (263 mg, yield 81%), which was vacuum dried for 16 hours and then used for later use;
[0054] (2) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water, and alcohol in sequence, and drying the FTO glass after cleaning to obtain a clean FTO glass substrate; sputtering a 3% Cu-doped nickel oxide target on the clean FTO glass substrate layer to obtain a 40 nm nickel oxide hole transport layer;
[0055] (3) First, 1 mg of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate was weighed and dissolved in 1 mL of isopropanol. After stirring to clarify, a phenylacetylhydrazine·5-phenyl-2,4-pentadienoate isopropanol solution was obtained. Subsequently, the phenylacetylhydrazine·5-phenyl-2,4-pentadienoate isopropanol solution was slit-coated on a substrate covered with a nickel oxide hole transport layer. After coating, a heat treatment was performed at 100° C. for 10 min to obtain a nickel oxide hole transport layer with a phenylacetylhydrazine·5-phenyl-2,4-pentadienoate additive interface modified.
[0056] (4) Weighing CsI, MAI, FAI, and PbI2 powders (molar ratio of 0.05:0.15:0.8:1.08) and dissolving them in a mixed solvent of 2-methoxyethanol and N-methylpyrrolidone (volume ratio of 9:1), stirring and clarifying to obtain a 1.2 mol / L perovskite precursor solution; slit coating the perovskite precursor solution on a nickel oxide hole transport layer substrate covered with an interface modified with a phenylacetylhydrazine·5-phenyl-2,4-pentadienoic acid additive, and heat treating the coated perovskite wet film at 120°C for 20 min to obtain a 500 nm thick perovskite light absorbing layer;
[0057] (5) A 50 nm thick C60 electron transport layer is sequentially evaporated on the perovskite light absorbing layer, a 10 nm thick tin oxide interface buffer layer is reactively plasma deposited, and a 500 nm thick IZO electrode layer is sputtered to obtain a perovskite solar cell without multifunctional additives.
[0058] Comparative Example 3:
[0059] A perovskite solar cell (PTAA type) without multifunctional additives and a preparation method thereof, comprising the following steps:
[0060] (1) ultrasonically cleaning FTO glass with glass cleaning agent, ultrapure water and alcohol in sequence, and drying after cleaning to obtain a clean FTO glass substrate; slit coating 2.2 mg / mL PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) chlorobenzene solution on the clean FTO glass substrate layer, and heat treating at 100°C for 10 min after coating to obtain a 20 nm PTAA hole transport layer;
[0061] (2) Weighing CsI, MAI, FAI, and PbI2 powders (molar ratio of 0.05:0.15:0.8:1.08) and dissolving them in a mixed solvent of 2-methoxyethanol and N-methylpyrrolidone (volume ratio of 9:1), stirring and clarifying to obtain a 1.2 mol / L perovskite precursor solution; slit coating the perovskite precursor solution on a substrate covered with a PTAA hole transport layer, and heat treating the coated perovskite wet film at 120°C for 20 min to obtain a 500 nm thick perovskite light absorbing layer;
[0062] (3) A 50 nm thick C60 electron transport layer is sequentially evaporated on the perovskite light absorbing layer, a 10 nm thick tin oxide interface buffer layer is reactively plasma deposited, and a 500 nm thick IZO electrode layer is sputtered to obtain a perovskite solar cell (PTAA type) without multifunctional additives.
[0063] Comparative Example 4:
[0064] A perovskite solar cell (PTAA type) based on a multifunctional additive and a preparation method thereof, comprising the following steps:
[0065] (1) 150.18 mg (1 mmol) of phenylacetyl hydrazine was weighed and dissolved in 15 mL of anhydrous ethanol, 174.196 mg (1 mmol) of 5-phenyl-2,4-pentadienoic acid was weighed and dissolved in 2 mL of anhydrous ethanol, and the 5-phenyl-2,4-pentadienoic acid ethanol solution was slowly added dropwise to the continuously stirred phenylacetyl hydrazine ethanol solution. The reaction temperature was kept at zero degrees during the reaction process, and nitrogen was introduced for protection. After the addition was completed, stirring was continued for 20 minutes, and phenylacetyl hydrazine·5-phenyl-2,4-pentadienoic acid crude product was obtained by rotary evaporation. Finally, the crude product was washed four times with ethyl acetate and ether in turn to obtain pure phenylacetyl hydrazine·5-phenyl-2,4-pentadienoic acid salt (263 mg, yield 81%), which was vacuum dried for 16 hours and then used for later use;
[0066] (2) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water, and alcohol in sequence, and drying after cleaning to obtain a clean FTO glass substrate; slit coating a 2.2 mg / mL PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) chlorobenzene solution on the clean FTO glass substrate layer, and heat treating at 100°C for 10 min after coating to obtain a 20 nm PTAA hole transport layer;
[0067] (3) First, weigh CsI, MAI, FAI, and PbI2 (molar ratio of 0.05:0.15:0.8:1.08) powders and dissolve them in a mixed solvent of 2-methoxyethanol and N-methylpyrrolidone (volume ratio of 9:1). Stir to clarify to obtain a 1.2 mol / L perovskite precursor solution. Then weigh 3 mg of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate and add it to 1 mL of the perovskite precursor solution. Stir to completely dissolve to obtain a perovskite precursor solution containing phenylacetylhydrazine·5-phenyl-2,4-pentadienoate additives. Slit-coat the perovskite precursor solution containing phenylacetylhydrazine·5-phenyl-2,4-pentadienoate additives on a substrate covered with a PTAA hole transport layer. The coated perovskite wet film is heat treated at 120°C for 20 min to obtain a 500 nm thick perovskite light absorbing layer.
[0068] (4) A 50 nm thick C60 electron transport layer is sequentially evaporated on the perovskite light absorbing layer, a 10 nm thick tin oxide interface buffer layer is reactively plasma deposited, and a 500 nm thick IZO electrode layer is sputtered to obtain a perovskite solar cell (PTAA type) based on a multifunctional additive.
[0069] Comparative Example 5:
[0070] A multifunctional additive interface-modified perovskite solar cell (PTAA type) and a preparation method thereof, comprising the following steps:
[0071] (1) 150.18 mg (1 mmol) of phenylacetyl hydrazine was weighed and dissolved in 15 mL of anhydrous ethanol, 174.196 mg (1 mmol) of 5-phenyl-2,4-pentadienoic acid was weighed and dissolved in 2 mL of anhydrous ethanol, and the 5-phenyl-2,4-pentadienoic acid ethanol solution was slowly added dropwise to the continuously stirred phenylacetyl hydrazine ethanol solution. The reaction temperature was kept at zero degrees during the reaction process, and nitrogen was introduced for protection. After the addition was completed, stirring was continued for 20 minutes, and phenylacetyl hydrazine·5-phenyl-2,4-pentadienoic acid crude product was obtained by rotary evaporation. Finally, the crude product was washed four times with ethyl acetate and ether in turn to obtain pure phenylacetyl hydrazine·5-phenyl-2,4-pentadienoic acid salt (263 mg, yield 81%), which was vacuum dried for 16 hours and then used for later use;
[0072] (2) ultrasonically cleaning the FTO glass with a glass cleaning agent, ultrapure water, and alcohol in sequence, and drying after cleaning to obtain a clean FTO glass substrate; slit coating a 2.2 mg / mL PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) chlorobenzene solution on the clean FTO glass substrate layer, and heat treating at 100°C for 10 min after coating to obtain a 20 nm PTAA hole transport layer;
[0073] (3) First, 1 mg of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate was weighed and dissolved in 1 mL of isopropanol. After stirring to clarify, a phenylacetylhydrazine·5-phenyl-2,4-pentadienoate isopropanol solution was obtained. Subsequently, the phenylacetylhydrazine·5-phenyl-2,4-pentadienoate isopropanol solution was slit-coated on a substrate covered with a PTAA hole transport layer. After coating, a heat treatment was performed at 100° C. for 10 min to obtain a PTAA hole transport layer modified with a phenylacetylhydrazine·5-phenyl-2,4-pentadienoate additive interface.
[0074] (4) Weighing CsI, MAI, FAI, and PbI2 powders (molar ratio of 0.05:0.15:0.8:1.08) and dissolving them in a mixed solvent of 2-methoxyethanol and N-methylpyrrolidone (volume ratio of 9:1), stirring and clarifying to obtain a 1.2 mol / L perovskite precursor solution; slit coating the perovskite precursor solution on a PTAA hole transport layer substrate covered with an interface modified with a phenylacetylhydrazine·5-phenyl-2,4-pentadienoic acid additive, and heat treating the coated perovskite wet film at 120°C for 20 min to obtain a 500 nm thick perovskite light absorbing layer;
[0075] (5) A 50 nm thick C60 electron transport layer is sequentially evaporated on the perovskite light absorbing layer, a 10 nm thick tin oxide interface buffer layer is reactively plasma deposited, and a 500 nm thick IZO electrode layer is sputtered to obtain a multifunctional additive interface modified perovskite solar cell (PTAA type).
[0076] As shown in Table 1, the photoelectric conversion efficiency of the perovskite solar cell prepared with phenylacetylhydrazine·5-phenyl-2,4-pentadienoate additive is 23.59%, and the efficiency of the cell only decays by 4.3% after 1000 hours of maximum power point tracking. The device efficiency and stability are much better than other comparative devices, indicating that the addition of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate to the perovskite precursor solution can effectively improve the crystallization quality of the perovskite film, release the interfacial tensile stress, passivate the buried interface defects, and simultaneously improve the efficiency and stability of the perovskite cell.
[0077] Table 1. Performance parameters of products of examples and comparative examples
[0078]
[0079]
[0080] The perovskite precursor solutions with or without phenylacetylhydrazine·5-phenyl-2,4-pentadienoate were placed in the air for different periods of time, and the absorption edge wavelengths of the two perovskite precursor solutions placed for different periods of time were tested. Solar cells were prepared based on the two perovskite precursor solutions placed for different periods of time. Figure 2 and Figure 3 As shown in the figure, the color of the perovskite precursor solution with the addition of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate did not change much after being placed in the air for 30 days, and the concentration of iodine in the solution hardly increased, indicating that the addition of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate can significantly improve the long-term stability of the perovskite precursor solution and greatly inhibit the oxidation of the perovskite precursor solution; Figure 4 As shown, based on the perovskite precursor solution containing phenylacetylhydrazine·5-phenyl-2,4-pentadienoate placed for different times, the performance of the prepared perovskite solar cells remained basically unchanged, which also confirmed the excellent antioxidant properties of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate.
[0081] like Figure 5 As shown, perovskite solar cells were prepared under different relative humidity environments based on the presence or absence of the addition of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate perovskite precursor solution. The cell efficiency of the perovskite solar cells prepared using the perovskite precursor solution containing phenylacetylhydrazine·5-phenyl-2,4-pentadienoate in different relative humidity environments did not change significantly, indicating that the addition of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate effectively eliminated the effect of moisture in the air on the quality of perovskite film formation, thereby achieving the performance of perovskite cells prepared in a high humidity environment that is comparable to that prepared in a low humidity environment.
[0082] like Figure 6As shown, perovskite films were prepared based on the perovskite precursor solution with or without the addition of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate. After the addition of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate, the crystallization quality of the perovskite film was improved, the grain size was large, and the coverage was dense.
[0083] like Figure 7 As shown in (a) and (b), the XPS images of nickel and oxygen elements are shown, respectively, indicating that phenylacetylhydrazine·5-phenyl-2,4-pentadienoate can effectively reduce the high-valent Ni on the surface of nickel oxide. 3+ Ions. Figure 8 As shown, (a) and (b) correspond to the presence or absence of phenylacetylhydrazine·5-phenyl-2,4-pentadienoate (2θ is the diffraction angle), respectively. The perovskite film is deposited on nickel oxide using a perovskite precursor solution with phenylacetylhydrazine·5-phenyl-2,4-pentadienoate additive. The stability of the perovskite film is greatly improved. It only begins to decompose after being placed in the air for 60 days, and a small amount of lead iodide is precipitated.
[0084] Therefore, combined with Figure 2-8 As shown in the figure, the perovskite precursor solution with phenylacetylhydrazine·5-phenyl-2,4-pentadienoate additive can still produce device performance comparable to that produced in a low humidity environment in high humidity air, with high device performance consistency, which greatly extends the service life of the perovskite precursor solution, which is particularly critical for the large-scale batch preparation of perovskite cells. At the same time, the strong reducing property of the additive effectively passivates the buried nickel oxide interface, eliminates the damage of the buried interface defects to the stability of the perovskite lattice, and significantly improves the photoelectric conversion efficiency and stability of perovskite solar cells, which has high commercial application potential.
[0085] The above description is only a preferred experimental example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A perovskite solar cell based on a multifunctional additive, characterized in that: The perovskite solar cell comprises, from bottom to top, a transparent conductive substrate layer, a hole transport layer, a perovskite light absorption layer, an electron transport layer, an interface buffer layer and an electrode layer, wherein the perovskite light absorption layer contains a multifunctional additive; The general structural formula of the multifunctional additive is X·Y, wherein X is a hydrazine compound, including one of phenylhydrazine, benzylhydrazine, phenethylhydrazine, phenylpropylhydrazine, benzoylhydrazine, and phenylacetylhydrazine; and Y is a reducing acid compound, including one of formic acid, hypophosphorous acid, benzenesulfinic acid, methanesulfinic acid, 2,4-hexadienoic acid, 5-phenyl-2,4-pentadienoic acid, 2,4,6,8-decatetraenoic acid, 3,4,5-trihydroxybenzoic acid, 3,5-dihydroxyphenylacetic acid, 4-hydroxyphenylacetic acid, p-hydroxybenzoic acid, and 3,5-dihydroxybenzoic acid.
2. The perovskite solar cell based on a multifunctional additive according to claim 1, characterized in that: The transparent conductive substrate layer is made of FTO glass, ITO glass, ITO / PET, ITO / PEN or ITO / PI.
3. The perovskite solar cell based on a multifunctional additive according to claim 1, characterized in that: The hole transport layer is made of nickel oxide or doped nickel oxide, and has a thickness of 1 to 100 nm.
4. The perovskite solar cell based on a multifunctional additive according to claim 1, characterized in that: The general structural formula of the perovskite light-absorbing layer is ABX3, and the thickness is 100 to 2000 nm, wherein A is Cs + 、MA + or FA + , B is Pb 2+ Sn 2+ Or Ge 2 + , X is I - Br - or Cl - .
5. The perovskite solar cell based on a multifunctional additive according to claim 1, characterized in that: The electron transport layer is fullerene and its derivatives, and has a thickness of 1 to 100 nm.
6. The perovskite solar cell based on a multifunctional additive according to claim 1, characterized in that: The interface buffer layer is made of bathocuproin, tin oxide, zinc oxide, yttrium oxide, cerium oxide, titanium oxide or niobium oxide, and has a thickness of 1-100 nm.
7. The perovskite solar cell based on a multifunctional additive according to claim 1, characterized in that: The electrode layer is made of Cu, Ag, Au, Mo, ITO, IZO or AZO, and has a thickness of 10 to 10000 nm.
8. The method for preparing a perovskite solar cell based on a multifunctional additive according to any one of claims 1 to 7, characterized in that: include: (1) Synthesize multifunctional additives; (2) depositing a hole transport layer on a clean transparent conductive substrate layer; (3) dissolving the perovskite powder in an organic solvent, stirring and clarifying to form a perovskite precursor solution, adding a multifunctional additive, and dissolving it completely to obtain a perovskite precursor solution containing the multifunctional additive, coating or printing the perovskite precursor solution containing the multifunctional additive on the hole transport layer and heat treating it to obtain a perovskite light absorbing layer; (4) An electron transport layer, an interface buffer layer, and an electrode layer are sequentially deposited on the perovskite light absorbing layer to obtain a perovskite solar cell based on a multifunctional additive.
9. The preparation method according to claim 8, characterized in that: The deposition method of the hole transport layer is selected from evaporation, sputtering, chemical vapor deposition, coating, and printing; the deposition method of the electron transport layer is evaporation; the deposition method of the interface buffer layer is selected from evaporation, sputtering, reactive plasma deposition, chemical vapor deposition, coating, and printing; the deposition method of the electrode layer is selected from evaporation, sputtering, chemical vapor deposition, coating, and printing.
10. The method for preparing a perovskite solar cell based on a multifunctional additive according to claim 8, characterized in that: In step (2), the organic solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol, and acetonitrile, the concentration of the perovskite precursor solution is 0.1 to 3 mol / L, the concentration of the multifunctional additive in the perovskite precursor solution containing the multifunctional additive is 0.001 to 50 mg / mL, the heat treatment temperature is 30 to 300° C., and the time is 5 to 120 minutes.